1995
DOI: 10.1123/pes.7.1.69
|View full text |Cite
|
Sign up to set email alerts
|

The Reliability and Validity of the 20-Meter Shuttle Test as a Predictor of Peak Oxygen Uptake in Edinburgh School Children, Age 13 to 14 Years

Abstract: This study examined the reliability and validity of the 20-meter shuttle test as a predictor of peak VO2 in Edinburgh school children. Thirty-three children (15 boys, 18 girls) performed three shuttle tests and three laboratory treadmill tests of peak VO2. Multiple regression analysis revealed that the prediction of peak VO2 (ml·kg−1·min−1) from shuttle run performance was improved by including skinfold thickness measurements in the prediction models, particularly with the female group. Predictive power was gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 0 publications
4
35
3
Order By: Relevance
“…Sub-analysis of the validity of the 9-minute test by gender revealed differences, with higher validity in male subjects (r=0.59) as compared to female subjects (r=0.43); in males, the test explained 35% of results, versus 18% of results in female subjects. This is consistent with the results reported in previous studies of other field tests for estimation of CRF, which showed superior validity in male subjects [21][22][23] . Careful interpretation of this analysis of the validity of the 9-minute test is warranted, as analysis based solely on the 9-minute distance does not permit comparison between VO 2 peak values and absolute VO 2 values measured during the test itself.…”
Section: Discussionsupporting
confidence: 83%
“…Sub-analysis of the validity of the 9-minute test by gender revealed differences, with higher validity in male subjects (r=0.59) as compared to female subjects (r=0.43); in males, the test explained 35% of results, versus 18% of results in female subjects. This is consistent with the results reported in previous studies of other field tests for estimation of CRF, which showed superior validity in male subjects [21][22][23] . Careful interpretation of this analysis of the validity of the 9-minute test is warranted, as analysis based solely on the 9-minute distance does not permit comparison between VO 2 peak values and absolute VO 2 values measured during the test itself.…”
Section: Discussionsupporting
confidence: 83%
“…Several authors (Leger et al 1988;Matsuzaka et al 2004;McVeigh et al 1995) suggest the best estimations of peak VO 2 are from those equations that include BMI or skinfold thickness, age and gender (Barnett et al 1993;Fernhall et al 1998;Matsuzaka et al 2004) rather than those that included age only (Leger et al 1988). It has been suggested that, in addition to chronological age, biological maturation inXuences the relationship between peak VO 2 and 20-m MSRT performance (Leger et al 1988).…”
Section: Discussionmentioning
confidence: 97%
“…However, Barnett et al (1993) studying 55 Hong Kong Chinese students (27 boys and 28 girls, ages 12-17 years) found that an inclusion of gender in the regression equations used to predict peak VO 2 determined in laboratory improved the accuracy of prediction. Boreham et al (1990) indicated a higher correlation between the 20-m MSRT and peak VO 2 in a group of 24 schoolgirls (15.4 years) than in a group of 24 schoolboys (15.6 years) (r = 0.90 vs. r = 0.64, respectively), and McVeigh et al (1995) found that the plot of peak VO 2 measured in laboratory against the 20-m MSRT performance showed distinct gender groups and divergent regression lines for boys and girls (15 boys, 18 girls). Barnett et al (1993) and Leger et al (1988) also identiWed age as a critical variable.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations